The increased prevalence of Trichomonas vaginalis in a scenario of cervical cancer screening without cytology O aumento da prevalência de Trichomonas vaginalis em um cenário de triagem de câncer cervical sem citologia - Eleutério Junior, José; Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 2017)
There is currently a strong trend in developed countries and in some developing countries to start adopting the screening of preinvasive lesions of cervical cancer through molecular biology techniques, placing the cytology (Pap smear), in some schemes, as a helper method of positive cases screening. In other flowcharts, cytology is no longer used, and the positive cases for human papillomavirus (HPV) are subjected to triage in other ways (such as HPV genotyping), or forwarded straight to colposcopy. [...]